2019
DOI: 10.1002/anie.201811834
|View full text |Cite
|
Sign up to set email alerts
|

Paintable Room‐Temperature Phosphorescent Liquid Formulations of Alkylated Bromonaphthalimide

Abstract: Organic phosphors have been widely explored with an understanding that crystalline molecular ordering is arequisite for enhanced intersystem crossing. In this context, we explored the room-temperature phosphorescence features of asolvent-free organic liquid phosphor in air.While alkyl chain substitution varied the physical states of the bromonaphthalimides,t he phosphorescence remained unaltered for the solvent-free liquid in air.A st he first report, as olvent-free liquid of al ong swallow-tailed bromonaphtha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 50 publications
0
52
0
Order By: Relevance
“…[ 20 ] However the large Δ E ST (singlet–triplet energy splitting) always subsidizes these organics unobservable RTP effect, and a few methods have been reported to overcome this obstacle. [ 7h,8c,21 ] Here, electron donor of Aba‐ x was attached to 1,8‐naphthalimide (18‐NI) and 2,3‐naphthalimide (23‐NI), respectively, to obtain two kinds of NNI derivatives sharing the same electron‐deficient NNI ring, namely Naba‐ x and Npaba‐ x ( x = o , m , or p ). Surprisingly, a yellow RTP with peaks centered at 548, 593, and 635 nm was obtained from Naba‐ x ( x = o , m , or p ) doped series in 1 with the highest τ p of 311.6 ms for Naba‐ o /‐Cl ( Figure a–c,g).…”
Section: Resultsmentioning
confidence: 99%
“…[ 20 ] However the large Δ E ST (singlet–triplet energy splitting) always subsidizes these organics unobservable RTP effect, and a few methods have been reported to overcome this obstacle. [ 7h,8c,21 ] Here, electron donor of Aba‐ x was attached to 1,8‐naphthalimide (18‐NI) and 2,3‐naphthalimide (23‐NI), respectively, to obtain two kinds of NNI derivatives sharing the same electron‐deficient NNI ring, namely Naba‐ x and Npaba‐ x ( x = o , m , or p ). Surprisingly, a yellow RTP with peaks centered at 548, 593, and 635 nm was obtained from Naba‐ x ( x = o , m , or p ) doped series in 1 with the highest τ p of 311.6 ms for Naba‐ o /‐Cl ( Figure a–c,g).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, such LMLs often exhibit low viscosities. For instance, the LMLs of alkylated tetrazines and alkylated naphthalenes exhibit complex viscosities (η*) in the ranges of 28–58 and 38–67 mPa • s, respectively, which are much lower than the η* of alkylated oligo( p ‐phenylenevinylene)s (0.64–34.6 Pa • s), alkylated 9,10‐diphenylanthracenes (0.28–84.0 Pa • s), alkylated pyrenes (2.3–58.0 Pa • s), and an alkylated bromonaphthalimide (0.79 Pa • s) . Such low viscous LMLs are promising for developing refreshable devices owing to their facile refilling.…”
Section: Design Principles Of Lmlsmentioning
confidence: 99%
“…Quite recently, Babu's group reported the first room‐temperature metal‐free phosphorescent LML, BNT1 , using bromonaphthalimide as a phosphor . The attachment of long bulky alkyl chains resulted in a low T g (<−38.7 °C) of BNT1 , which behaves as a liquid at room temperature ( Figure a,b).…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite multifarious examples of RTP in the crystalline state, purely organic compounds showing RTP in solution are rare [ 64 69 ]. Takeuchi et al [ 28 ] reported a bromofluorenecarbaldehyde 2 which shows blue fluorescence in chloroform at 298 K under air and green phosphorescence under argon with a phosphorescence quantum yield of Φ P = 5.9% ( Fig.…”
Section: Introductionmentioning
confidence: 99%